BRANDING AND THE STAGES OF ITS FORMATION (Eureka Journal of Language, Culture & Social Change, 2025)
This article examines the concept of branding, its historical development, and its role within the modern marketing system. Particular attention is given to the economic and communicative significance of branding, the evolution of branding practices, brand identity, core brand elements, and brand equity. The study highlights strategic approaches to brand management, mechanisms for creating a sustainable brand image in consumers’ minds, and key factors contributing to brand value enhancement. The findings of the research are of both theoretical and practical importance for marketing, advertising, and public relations professionals, as well as researchers and university students.
Keywords: branding, brand identity, brand equity, brand value, marketing communications, brand management.